PERBAIKAN KUALITAS RENGGINANG UBI KAYU TANPA FERMENTASI - Setiawati, Bernadetta Budi (Jurnal Ilmu-Ilmu Pertanian, 2019)
Cassava rengginang, a Javanese traditional snack food still shows cloudy white colour and no or very slight expansion when fried that are considered as a problem of undesired quality. Additional fermentation process in its manufacturing seems to be able to solve the problem. Fermentation process applied to the cassava rengginang manufacturing will affect its quality, especially the crispness, expansion capacity and taste. The crispness would possibly bring about irritation to both the throat and tongue in a little bit longer and more consumption. Two factors possibly influencing the above problem are frequency of washing process and total amount of starch resulted from every washing process, are taken as treatments. Organoleptic evaluation involving tests on texture, aroma, taste, crispness and levels of consumer preferences is taken as a variable response. The experimental design consisting of once, twice, three times and without washing process and total amount of starch related to the frequencies of the washing process was conducted to seek the best combination of the treatments that was automatically resulting in the highest variable response. Investigation tests, conducted on the fried non fermented cassava rengginang, show that the combination of three time washing process related to 244.38 grams cassava starch, 30.50 gram residue with 3 litters of water is significantly the best and preferred more than that of currently available in local markets.